2021
DOI: 10.3390/su13041786
|View full text |Cite
|
Sign up to set email alerts
|

Re-Naturing the City: Linking Urban Political Ecology and Cultural Ecosystem Services

Abstract: In the last few decades European industrial cities have experienced major transformations which have implied the need to rethink the role of nature. Re-naturing the city, reconnecting urban planning and nature and enhancing sustainability, means taking into account ecosystems and biodiversity through a social approach to nature which reconsiders nature as a social product and re-examines city–nature relationships, the way Urban Political Ecology (UPE) suggests. This paper focuses on the Brescia Quarry Park, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 93 publications
0
9
0
2
Order By: Relevance
“…Transformation of former industrial landscapes has mostly focused on older industrial areas and harbours, which are often close to inner cities and lend heritage values and visual significance to transformation projects [9][10][11][12]. Many of these old industrial areas are now redeveloped and re-urbanised, and a similar process is encompassing industrial areas in the suburbs [13,14]. Due to continued urban growth, the YILs in the suburbs or outskirts of large cities are next in line [15].…”
Section: Tabula Rasa Approach Versus Landscape-based Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Transformation of former industrial landscapes has mostly focused on older industrial areas and harbours, which are often close to inner cities and lend heritage values and visual significance to transformation projects [9][10][11][12]. Many of these old industrial areas are now redeveloped and re-urbanised, and a similar process is encompassing industrial areas in the suburbs [13,14]. Due to continued urban growth, the YILs in the suburbs or outskirts of large cities are next in line [15].…”
Section: Tabula Rasa Approach Versus Landscape-based Transformationmentioning
confidence: 99%
“…These principles also shaped the suburban context across Europe and North America. Other studies have identified, investigated or mentioned similar post-industrial landscapes in Belgium, Italy, Germany, Great Britain, and the USA [14,[21][22][23][24][25]. Given that YILs cover vast expanses of land-up to 25% of the total area in some Danish suburbs-our understanding of these landscapes is astonishingly limited [15,26].…”
Section: Young Industrial Landscapes and Their Transformation Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…L'osservazione partecipante, condotta in seno alla Consulta, ha permesso di ricostruire le dinamiche di potere sottostanti le politiche intraprese nell'area. Le diverse azioni progettuali, in particolare le interviste e laboratori per una mappatura partecipata dei valori ecologici dell'area del Parco delle Cave (Tononi e Pietta, 2020;Pietta e Tononi, 2021), hanno coinvolto la popolazione e la loro conoscenza ecologico-culturale dell'area svelando le relazioni socio-ecologiche.…”
Section: Fig 1 -Il Sistema Socio-naturale DI Bresciaunclassified
“…Una parte della cittadinanza vede alcuni laghi come luogo per attività escursionistiche o sportive, vivendo il parco come grande area di intrattenimento e contatto con la natura. Un'altra parte punta invece sulla necessità di proteggere la biodiversità di tali luoghi e ritiene eccessivamente impattanti su flora e fauna le azioni di rinaturalizzazione portate avanti (Pietta e Tononi, 2021).…”
Section: Fig 1 -Il Sistema Socio-naturale DI Bresciaunclassified